Helper and suppressor activities of an autoreactive mouse thyroglobulin-specific T-cell clone. - Champion, B R (1986)
An autoreactive T-cell clone, MTg9B3, specific for mouse thyroglobulin, has been characterized. This clone has properties consistent with it an being autoreactive T helper cell. It is I-A restricted, with a surface phenotype of Thy 1+, L3T4+, Ly2-, and produces a number of non-specific lymphokine activities following specific triggering with antigen. Furthermore, antigen-stimulated clone cells were capable of providing bystander help in SRBC-specific antibody responses. Surprisingly, MTg9B3 cells had a profound suppressive effect on thyroglobulin autoantibody responses in vitro.